2023
DOI: 10.3233/jvr-221224
|View full text |Cite
|
Sign up to set email alerts
|

Vocational rehabilitation service delivery: Technical assistance needs of vocational rehabilitation professionals

Abstract: BACKGROUND: Americans with disabilities have historically faced substantial barriers to employment participation. The state-federal vocational rehabilitation (VR) program has played an important role in increasing the employment opportunities of Americans with disabilities through the provision of services and supports designed to lead to high-quality employment, independence, self-sufficiency, and full integration into the community. OBJECTIVE: The Vocational Rehabilitation Technical Assistance Center for Qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Alternatively, the capacity of SVRAs regarding the development of the implementation of CE consistent with federal guidance, conceptual overlap with supported employment, or even community-based providers’ preparedness to provide CE services consistent with SVRA policies or contracts may have affected the utilization of CE over the last several years. However, a recent national needs assessment of SVRAs and their affiliates indicated that CE was a relatively lower priority in regard to technical assistance and training relative to greater needs of SVRAs in areas such as customized training, business outreach, and even the highly associated service area of supported employment (Tansey et al, in press). CE may be viewed as less of priority among the range of challenges and opportunities that SVRAs have in relation to increasing participation of persons with disabilities in their services (Lee et al, in press; Tansey et al, in press), particularly looking at transition-age youth with disabilities (Friedman et al, in press); increasing the quality of employment outcomes through services such as customized training, work-based learning, and apprenticeships (Tansey et al, in press); and ultimately, engaging and supporting businesses as part of a larger dual-customer approach in the recruitment (Iwanaga et al, 2018), hiring (Grenawalt et al, in press), and retention of people with disabilities in the workforce (Chen et al, in press; Wu et al, in press).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the capacity of SVRAs regarding the development of the implementation of CE consistent with federal guidance, conceptual overlap with supported employment, or even community-based providers’ preparedness to provide CE services consistent with SVRA policies or contracts may have affected the utilization of CE over the last several years. However, a recent national needs assessment of SVRAs and their affiliates indicated that CE was a relatively lower priority in regard to technical assistance and training relative to greater needs of SVRAs in areas such as customized training, business outreach, and even the highly associated service area of supported employment (Tansey et al, in press). CE may be viewed as less of priority among the range of challenges and opportunities that SVRAs have in relation to increasing participation of persons with disabilities in their services (Lee et al, in press; Tansey et al, in press), particularly looking at transition-age youth with disabilities (Friedman et al, in press); increasing the quality of employment outcomes through services such as customized training, work-based learning, and apprenticeships (Tansey et al, in press); and ultimately, engaging and supporting businesses as part of a larger dual-customer approach in the recruitment (Iwanaga et al, 2018), hiring (Grenawalt et al, in press), and retention of people with disabilities in the workforce (Chen et al, in press; Wu et al, in press).…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent national needs assessment of SVRAs and their affiliates indicated that CE was a relatively lower priority in regard to technical assistance and training relative to greater needs of SVRAs in areas such as customized training, business outreach, and even the highly associated service area of supported employment (Tansey et al, in press). CE may be viewed as less of priority among the range of challenges and opportunities that SVRAs have in relation to increasing participation of persons with disabilities in their services (Lee et al, in press; Tansey et al, in press), particularly looking at transition-age youth with disabilities (Friedman et al, in press); increasing the quality of employment outcomes through services such as customized training, work-based learning, and apprenticeships (Tansey et al, in press); and ultimately, engaging and supporting businesses as part of a larger dual-customer approach in the recruitment (Iwanaga et al, 2018), hiring (Grenawalt et al, in press), and retention of people with disabilities in the workforce (Chen et al, in press; Wu et al, in press). Even the task of working to address system issues impacting SVRA outcomes, such as transportation (Bezyak et al, in press), may represent the greater existential threat to CIE and be identified as a higher priority than the development of CE services.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, persons with disabilities, particularly youth, are more than twice as likely to live in poverty as their peers without disabilities (Houtenville & Boege, 2019). To address low labor force participation of persons with disabilities, leaders of state vocational rehabilitation agencies (SVRA) have indicated a lack of evidence-based practices, or practices identified through applied research, and subsequent knowledge translation and transfer to SVRAs through technical assistance (Tansey & Anderson, 2017).…”
mentioning
confidence: 99%
“…vocational rehabilitation agencies (SVRAs) have pointed to a lack of evidence-based practices (i.e., practices identified through applied research) and subsequent knowledge translation and transfer to SVRAs through technical assistance (Tansey & Anderson, 2017).…”
mentioning
confidence: 99%
“…As a result, persons with disabilities, and particularly youth, are more than twice as likely to live in poverty as their peers without disabilities (Houtenville & Boege, 2019). To address low labor force participation of persons with disabilities, leaders of state vocational rehabilitation agencies (SVRAs) have pointed to a lack of evidence-based practices (i.e., practices identified through applied research) and subsequent knowledge translation and transfer to SVRAs through technical assistance (Tansey & Anderson, 2017).…”
mentioning
confidence: 99%